ENDOPHYTIC FUNGI: BIODIVERSITY AND FUNCTIONS - M. MISHRA; R. PRASAD; A. VARMA (International Journal of Pharma and Bio Sciences, 2015)
Fungal endophytes are broad spectrum microorganisms which colonizes the plants without causing any symptoms. They occur ubiquitously in all plants, including a wide range of hosts in ecosystems. During the course of co-evolution, a mutualistic relationship occurs between endophytes and their host plant. Their population is influenced by location and climatic condition of host. In recent years remarkable attention is given to their ability to produce useful bioactive compounds for plant growth, protection and their sustenance in certain hostile condition. The present review focuses on the diversity, classification and beneficial roles of fungal endophytes and their significance on host plants and the future applications.